Spectroscopically pure metal vapor source for highly charged ion spectroscopy and capillary discharge soft x-ray lasers - Tomasel, F G; Shlyaptsev, V N; Rocca, J J (Review of scientific instruments, 2008)
We describe a compact, pulsed metal vapor source used for the production of dense plasma columns of interest for both soft x-ray laser research and spectroscopy of highly ionized plasmas. The source generates spectroscopically pure cadmium vapor jets in a room-temperature environment by rapidly heating an electrode with a capacitive discharge. In the configuration described herein, the metal vapor jet produced by the source is axially injected into a fast (up to 15 kA/ ns), high current (up to 200 kA peak) capillary discharge to generate highly ionized cadmium plasma columns. Spectroscopic analysis of the discharge emission in the 12-25 nm spectral range evidences the dominance of Cu-like (CdXX) and Ni-like (CdXXI) lines and shows strong line emission at 13.2 nm from the 4d (1)S(0)-4p (1)P(1) laser transition of Ni-like Cd. Hydrodynamic/atomic physics simulations performed to describe the dynamics of the plasma column and compute the optimum discharge conditions for laser amplification are discussed.